KEADILAN DALAM KERANGKA TEOLOGIS, FILOSOFIS DAN ETIK - Rahman Mantu (Institut Agama Islam Negeri (IAIN) Manado, 2017)
Abstract. Justice has been experiencing a kind of blurring of meaning. Because so many interpretations describe what is called theoretical justice, its limitations, and how it is implemented. There are many differences of opinion that lead to debate among western philosophers and between groups within Islam about the meaning of justice. Therefore the author tries to explain the meaning of theological, philosophical, and ethical perspective justice. The discussion will be limited to the thoughts of leaders related to the three aspects of justice. The predetermined figures have a concern with the theme of justice. The philosophers include Aristotle, Murthada Muthahari, Plato, and John Rawls. While among groups in Islam the authors of this paper include the Mu`tazilah with the Asy`ariyah. In the writing found that each of the philosophers and their groups had different understandings about interpreting justice whether in the theological, philosophical, and ethical domains. Keywords: Justice, Theological, Philosophical, Ethical, Islamic. Abstrak.Keadilan selama ini mengalami semacam pengkaburan makna. Karena begitu banyak tafsir dalam menguraikan apa itu yang disebut dengan keadilan secara teoritik, batasan-batasannya, serta bagaimana implementasinya. Banyak terjadi perbedaan pendapat yang mengtarah ke perdebatan dikalangan filosof barat maupun antar kelompok di dalam Islam tentang makna keadilan. Oleh karena itu penulis mencoba menjelaskan makna keadilan perspektif teologis, filosofis, dan etis. Pembahasan akan dibatasi dengan pemikiran-pemikiran tokoh terkait dengan tiga aspek keadilan tersebut. Tokoh-tokoh yang telah ditentukan memiliki konsern dengan tema keadilan.Para filosof itu diantaranya Aristoteles, Murthada Muthahari, Plato, serta John Rawls.Sedangkan antar kelompok dalam Islam yang penulis angkat dalam tulisan ini diantaranya Kaum Mu`tazilah dengan Kaum Asy`ariyah.Dalam tulisan mendapati bahwa masing-masing para filosof dan kelompoknya mempunyai pemahaman yang berbeda-beda tentang memaknai keadilan apakah itu dalam ranah teologis, filosofis, dan etik. Keywords:Keadilan, Teologis, Filosofis, Etik, Islam.